the effectiveness of new media on institutional communication systems in institutions - محمد عبد القادر عثمان علي (International Journal of Social Communication, 2021)
The research deals with the topic of the effectiveness of new media on institutional communication systems in institutions, the research came to identify the effectiveness of new media on institutional communication systems, and is it effective on institutional communication systems and is it active activities in achieving the goals and the extent of public interaction with activities and their effectiveness and the researcher used the survey method , Aiming at surveying methods of practice, and surveying public opinion, and the research concluded that new media and modern means of communication have an impact in serving the public and are doing what is necessary in institutional communication systems, therefore institutions must activate new media services, means and communication technology More modern, And that a large percentage of the research community does not know anything about the electronic crime law, and they use the new media periodically, which means increasing their exposure to these crimes, then the institutions should undertake an institutional communication process from the responsible authorities